HUBUNGAN TINGKAT KEBUGARAN JASMANI DENGAN AKLIMATISASI PENDAKI GUNUNG - Nurajab, Elzas (Jurnal Olahraga, 2019)
The This study aims to prove the relationship between the level of physical fitness towards the acclimatization of mountain climbers in the sireum sukabumi dampal nature lovers community. This research is a descriptive study with a correlational design. The population used was all the 20 dampal sireum nature lovers. The sampling technique uses total sampling taken from all populations. The sample was 20 people, the instruments used were the TKJI test and the questionnaire used to determine the results of acclimatization. The results of the study 1 person who possessed physical fitness level in the category did not experience Acute Mountain Sickness (AMS), 3 people who possessed physical fitness level in the category of less experienced Acute Mountain Sickness (AMS), 11 people who possessed physical fitness level in the category while not experiencing Acute Mountain Sickness (AMS), 1 person who possessed physical fitness level in good category did not experience Acute Mountain Sickness (AMS), while 3 people who possessed physical fitness level in the less experienced category Acute Mountain Sickness (AMS), while 1 people who have physical fitness levels in the category are experiencing Acute Mountain Sickness (AMS), the conclusion that the level of physical fitness of a climber does not have much effect on acclimatization that causes symptoms of Acute Mountain Sickness (AMS), because acclimatization is closely related to a person's adaptation process in a region with a weather he will face when at the place, several factors that influence such as the environment in which they live or their lifestyle habits.